THE EFFECT OF USING RANDOM PICTURE GAME TOWARD STUDENTS’ SPEAKING ABILITY AT THE SECOND SEMESTER STUDENTS OF BUSINESS ENGLISH STUDY PROGRAM OF BENGKALIS STATE POLYTECHNIC - Diah Paramita Sari (INOVISH JOURNAL, 2018)
Speaking skills has become the major priority to be taught between the four skills since communicative approach communication has been influenced in foreign language learning. Random Picture game is one of communicative technique that can motivate students in speaking English. This study aimed to find out the effect of using Random Picture Game toward students’ speaking ability at the second semester students of Business English Study Program. This research used experimental research design. It was conducted at State Polytechnic of Bengkalis. The design of this research was pre-experimental design with one group pretest and posttest. The population of this research was the second semester students with the total population was 20. The sample was taken by saturation sampling. This technique included all members of the population as the sample of the study. 20 students was the sample of this research. The result of this research was students who were taught by using random picture game had a significant effect toward speaking ability. In conclusion, random picture game can be used as a teaching technique in teaching speaking. For further researchers, this technique can be applied by English lecturers to other skills. Keywords: Speaking ability, random picture game, pre experimental design